Current Status and Future Outlook of Fuel Cell Vehicle Development in Toyota. (14th September 2015) - Kojima, Koichi; Fukazawa, Kazuhiro
Abstract : Fuel Cell Vehicle (FCV) can be one of the solutions to energy issues andclimate change. FCV has both environmentally-friendly and userfriendlyfeatures such as cruising range of more than 500km, coldstartability and about 3 minutes' refueling time. In December 2014, Toyota started selling the FCV called "MIRAI" in Japan. The FC systemis composed of Toyota-self-developed components like FC stack, FCboost converter and high pressure hydrogen tanks. The FC stack achievesthe maximum output of 114 kW and the volume power density of 3.1kW/L. Moreover, the FC stack doesn't require any external humidifier.The FC boost converter can boost the power generated in the FC stack to650 volts. The high pressure hydrogen tanks with three layers includingthe carbon fiber-reinforced plastic layer can store hydrogen at the veryhigh working pressure of 70 MPa to achieve the storage density of 5.7wt%.